Tilt? : the search for media bias - Niven, David, 1971- (Praeger, 2002)
Nine in ten Americans believe the media are biased. Trust in journalists ranks beneath that in lawyers, and even the media themselves regularly portray their own industry as slanted toward Democrats and liberals. These perceptions, however, do not coincide with reality, as David Niven reveals in his bold new take on an often-debated subject. Tilt? The Search for Media Bias presents the first comprehensive review of the charges, the evidence, and the effects, beginning with a simple but altogether overlooked premise: to measure media bias or fairness, one has to have a fair baseline with which to compare coverage. Using situations in which presidents, governors, mayors, and members of Congress from different political parties have produced the same results in office, Tilt? compares media coverage of Democrats and Republicans in situations in which they clearly deserved equal treatment. Niven's findings, unmistakable and consistent, reveal that when the output of politicians is the same, media coverage follows--a conclusion that is as provocative as it is timely and necessary.